Distinct AGO1 and AGO2 associated miRNA profiles in human cells and blood plasma - Turchinovich, Andrey; Burwinkel, Barbara (RNA biology, 2012)
Studies of miRNA association with Argonaute (AGO) proteins in mammalian cells have indicated lack of bias toward particular AGO. However, to our knowledge, the use of quantitative methods for studying miRNA association with different AGOs has not been reported so far. In this work we compared the total miRNA content in AGO1 and AGO2 immunoprecipitates obtained from MCF7 adenocarcinoma cells using TaqMan Low Density miRNA Arrays and successfully verified selected miRNAs with qPCR. For most of the miRNA species AGO1 and AGO2 profiles were well correlated, however, some miRNAs demonstrated consistent biases toward one of the Argonautes. Furthermore, miRNAs which were predominantly AGO2-associated derived mostly from sense strands of the corresponding pre-miRNAs while the majority of AGO1 biased miRNAs originated from antisense strands of the pre-miRNAs. Additionally, we show that circulating miRNA in human blood plasma can be immunoprecipitated with both AGO1 and AGO2 antibody. However, unlike in cell lysates, AGO1 and AGO2 associated miRNA profiles in plasma did not correlate, indicating that many cell types contribute to circulating miRNA (given that expression of AGO proteins is tissue specific). Furthermore, AGO-specific miRNA profiles in blood cells differed significantly from miRNAs profiles in plasma indicating that most circulating miRNAs are likely to derive from non-blood cells. Since circulating miRNAs hold great promise as biomarkers for numerous cancers and other diseases, we hypothesize that AGO-specific miRNA profiles might add an additional dimension to circulating miRNA-based diagnostics.
Gesehen am 17.09.2018